2012
DOI: 10.1017/cbo9781139104197
|View full text |Cite
|
Sign up to set email alerts
|

Cities and the Grand Tour

Abstract: How did eighteenth-century travellers experience, describe and represent the urban environments they encountered as they made the Grand Tour? This fascinating book focuses on the changing responses of the British to the cities of Florence, Rome, Naples and Venice, during a period of unprecedented urbanisation at home. Drawing on a wide range of unpublished material, including travel accounts written by women, Rosemary Sweet explores how travel literature helped to create and perpetuate the image of a city; wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In this, as with so many others who travelled during this period, Clerk was clearly tailoring his reports to ease anxieties back home. 76 Yet, Clerk III's curiosity, like that of his father decades earlier, pushed at these boundaries. In February 1696, Clerk entreated his father to permit him to travel that summer, with Italy as the ideal destination.…”
Section: Memories Of Having Perused His Father's Collection Framed Himentioning
confidence: 99%
See 1 more Smart Citation
“…In this, as with so many others who travelled during this period, Clerk was clearly tailoring his reports to ease anxieties back home. 76 Yet, Clerk III's curiosity, like that of his father decades earlier, pushed at these boundaries. In February 1696, Clerk entreated his father to permit him to travel that summer, with Italy as the ideal destination.…”
Section: Memories Of Having Perused His Father's Collection Framed Himentioning
confidence: 99%
“…While actions in contravention of parental will were by no means unusual among 'Grand Tourists', especially in the later eighteenth century, the collection as a whole suggests not only a wilful discarding of confessional façades, but a near-revelling in the newfound mixture of cosmopolitan chaos and opportunity. 92 Much of this correspondence passed through the hands of the tailor Charles Browne, a fellow Scot whose home was variously located by contemporary travellerswho typically referred to him as a 'sartore inglese'near the Strada di Condotti in Rome. Browne proved to be not only a welcoming host for Clerk, but also a ready source for Italian fashion: one bill from 8 July 1698, incorporating clothing of fine calico and silver buttons, reached nearly £30, while letters after his travels from Browne still provided connections for gun locks, 'stamps of the fountains', and fine gloves to the tune of eighteen Roman crowns.…”
Section: Memories Of Having Perused His Father's Collection Framed Himentioning
confidence: 99%
“…In her book on Italian cities and the Grand Tour, Rosemary Sweet argues that certain 'narratives […] were constructed around specific cities'. 10 Over the course of the eighteenth century Naples developed a reputation for hedonism and 'came to represent the antithesis of what many travellers believed to be the defining attributes of their own society'. 11 It did not have the same level of 'gambling and organised prostitution' as Venice; however, in the eyes of the English, Naples was a city that endangered its visitors' virtue and sexual morality.…”
Section: 'English Society' In Naplesmentioning
confidence: 99%
“…10 Over the course of the eighteenth century Naples developed a reputation for hedonism and 'came to represent the antithesis of what many travellers believed to be the defining attributes of their own society'. 11 It did not have the same level of 'gambling and organised prostitution' as Venice; however, in the eyes of the English, Naples was a city that endangered its visitors' virtue and sexual morality. This image was the result of a combination of factors, including the beauty and abundant fertility of the bay presided over by Mount Vesuviuswhose own unpredictability embodied Naples's reputation for riskand the early eighteenth-century rediscoveries of Pompeii and Herculaneum, which put Naples on the map as the ancient depraved playground of the wealthy Romans; and by the end of the period British society in Naples revolved around the disreputable household of the British ambassador, Sir William Hamilton.…”
Section: 'English Society' In Naplesmentioning
confidence: 99%
“…Roger Robertson felt he had to buy a second suit later on in his tour, even though he had purchased a new set of clothes in Paris. 114 In Italy, well-connected tourists found that they had access to high society in Turin or Florence, another inducement to dress up. Edward Thomas was invited to dine with the British ambassador in Turin, and therefore felt the pressure to buy more expensive clothing.…”
mentioning
confidence: 99%